Elaboração e validação de um questionário para avaliar conhecimentos, atitudes e práticas de médicos e enfermeiros da atenção primária à saúde sobre assistência ao pré-natal de baixo risco - Frisanco, Fernanda Menegatti (Universidade Federal de São Carlos, 2020)
Introduction: Primary Health Care provides universal access to services and comprehensive health care, in addition to organizing health systems, with positive impacts on the health of populations, especially the most vulnerable ones. Prenatal care has received great prominence in Primary Health Care, in order to guarantee care quality and humanization, promoting maternal and child well-being and impacts on maternal and perinatal morbidity and mortality. In this sense, the quality of a health service can be measured by the access to consumer goods as well as by the qualification of health professionals involved with prenatal care. The purpose of this study is the elaboration and validation of a questionnaire for studies of the Knowledge, Attitude and Practice of health professionals, specifically aimed at identifying these aspects in the assistance they provided in prenatal care. Objective: To develop and validate a questionnaire, using the methodology based, assessing the knowledge, attitudes and practices of Primary Health Care doctors and nurses about low-risk prenatal care. Methods: It is research with methodology based on Knowledge, Attitudes and Practices. It was developed with health professionals from the health units of Primary Health Care in a city in the interior of São Paulo. The steps of this study were: elaboration of the questionnaire based on recommendations from the area federations and technical manuals from the Ministry of Health, Brazilian Federation of Gynecology and Obstetrics Associations and in the quick consultation manual for UNICAMP health professionals, reviewed by two experts in the medical field. Subsequently, the questionnaire was validated by 24 health professionals, doctors and nurses who work in prenatal care, selected by simple randomization. The data collected with the professionals were tabulated in Microsoft Excel 2010 spreadsheets, with a quantitative analysis inferring how much the questions were properly understood by the respondents, the variability with which they were interpreted by them and how much the questionnaire was able to identify the points of interest to the research, as well as validating the intelligibility, the precision of the interpretability and the accuracy of the questions. Results: The results were presented through the responses obtained by the participants and are described in a table. In the topic Knowledge, eight conditions were demonstrated in relation to the care of pregnant women during prenatal care in Primary Health Care in which the participants marked right or wrong, the answers corresponded to more than 60% of correct answers, according to what the literature judges it correct; Also in this topic, some clinical cases were made available with the following contents: routine laboratory tests of prenatal care, risk factors for some health conditions, diagnosis and treatment of some common conditions during pregnancy, control of subsequent consultations, vaccination and shared care . In the topic of attitudes, it brought the opinion of the participants in relation to questions about the role of professionals in relation to the care of pregnant women during prenatal care. Most participants (82%) demonstrated positive attitudes towards this type of care. However, the positivity index for questions 19 and 24 was below 42%. In the topic of practices, the answers about the practices of the participants in relation to the care of pregnant women during prenatal care, highlighted that 100% of the participants presented positive practices about prenatal care. As for the critical assessment of the professionals in relation to the questionnaire, some suggestions for topics to be added to the instrument are highlighted, such as family planning, blood type and sexually transmitted infection during pregnancy. After the presentation of these results, the discussion took place, which was divided into two items: one that presents the characterization of the participants and the second with the responses and evaluation of the participants on the questionnaire, which resulted in the validation of the instrument. Considerations: It was concluded that the construction of the questionnaire and the analysis of the knowledge resulting from it allowed to validate the degree to which the questions were properly understood or misunderstood, the degree to which individuals within a group interpret the questions differently, the effectiveness of the questions in requesting adequate information and any areas of information that were invalided by the public of the proposed questionnaire. Its validation, following the steps proposed by the knowledge, attitudes and practices, allowed the conclusion of a version that is ready for future assessments of the knowledge, attitude and practice of professionals in the care of pregnant women, as well as showing clues as to the need for qualification of the professionals who provide assistance to low risk prenatal care in the Primary Health Care of this municipality.
Elaboration and validation of a questionnaire to assess knowledge, attitudes and practices of doctors and nurses of primary health care about low risk prenatal care
Keywords: Conhecimento; Atitude; Prática; Atenção primária à saúde; Cuidado pré-natal; Knowledge; Attitude; Practice; Primary health care; Prenatal care; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM OBSTETRICA